Internal Models of Motor Control: Reach Adaptation and Task Autism - Zuccaro, Laura (The Meducator, 2013)
The internal models theory is one of many hypotheses that aim to explain the mechanism of motor control in humans. The theory proposes that the central nervous system (CNS) forms neural representations of the external world, which are used to predict and adjust movements.1,2 Internal models have been well-studied, and this paper provides a general insight into the internal models theory before examining how subjects adapt during a reaching task.3 This reaching task, as explained via the internal models theory, will be compared between normal and disease states, specifically autism, a disorder of neural development. Through this comparison, it will be possible to determine how autistic patients differ in their motor abilities.